The Application of Planned Behavior Theory on Millennial Generation Behavior in Purchasing Organic Vegetables - Yusuf Ramadhan; Mukhamad Najib; Ma’mun Sarma (Jurnal Manajemen & Agribisnis, 2020)
Organic vegetables are vegetables that are cultivated without any synthetic chemicals. Organic vegetables production volume is increasing every year. There are expectations of increasing the annual production of organic food in order to provide safe and healthy food. Vegetables are one of the basic needs that are consumed daily in Indonesia. This research aimed to analyze the buying behavior of organic vegetables of millennials in Bandung city. This research tried to expand the Theory of Planned Behavior (TPB) by adding one variable, namely health consciousness, in the research framework. The methods used in this research were Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) with the AMOS approach. The number of samples used were was 208 respondents. Millennial Generation respondents consisted of people aged 21 to 40 years old whoi were selected with a sampling technique of quota sampling. Data collection was conducted by distributing online questionnaires using Google Forms via WhatsApp and Instagram. The results showed that the purchase intention variable had the most dominant influence toward on buying behavior. While health consciousness, which was an addition of the Theory of Planned Behavior modification, had the most dominant effect toward perceived behavioral control. Keywords: theory of planned behavior, health consciousness, organic vegetables, millennial generation, structural equation modeling (SEM)